Moral constraints on war principles and cases - Coppieters, Bruno; Fotion, Nick (Rowman & Littlefield, 2008)
This second edition of Moral Constraints on War offers a principle-by-principle presentation of the trans-cultural roots of the ethics of war in an age defined by the increasingly international nature of military intervention. Parts one and two trace the evolution of Just War Theory, analyzing the principles of jus ad bellum and jus in bello: the principles that determine under what conditions a war may be started and then conducted. Each chapter provides a historical background of the principle under discussion, an explanation of the principle, and numerous historical examples of its application. In Part three, case studies apply the theories discussed to NATO's humanitarian mission in Kosovo, terrorism and the Iraq War. Bringing together an international coterie of philosophers and political scientists, this accessible and practical guide offers students of military ethics and international relations rich, up-to-the-minute insight into the pluralistic character of Just War Theory.